Cocoa descriptors, their states and modus operandi - Engels, Jon M.M.; Bartley, Basil G.D.; Enríquez, Gustavo A. (CATIE, Turrialba (Costa Rica), 2015)
24 pág, ilus, 3 ref. Publicado también por CATIE, 1979. 24 p. (CATIE E57)